Political-Legal Strategies in Regulating Interfaith Marriage: An Analysis of Supreme Court Circular Letter in Indonesia - Solikhudin, Muhammad; Meidina, Ahmad Rezy; Zayyadi, Ahmad; Faidati, Ashima; Shufyansyah, Ikhdan Gimas; Zain, Muhammad Fuad; Faizah, Nur (Jurnal Ilmiah Al-Syir'ah, 2024)
This article examines the political and legal dimensions underlying the issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023, which addresses the issue of interfaith marriages in Indonesia. Through a qualitative approach employing doctrinal and socio-legal analysis, this study explores this policy's legislative intent, judicial implications, and broader societal impacts. The findings reveal that SEMA No. 2 of 2023 represents a strategic political-legal maneuver by the Indonesian judiciary to navigate the tension between religious norms, constitutional rights, and societal pluralism. While the circular aims to harmonize Islamic family law with Indonesia’s pluralistic legal framework, it has also sparked debates regarding its alignment with fundamental human rights principles and practical implications for legal certainty. This study contributes to the discourse on interfaith marriage regulation by offering a critical perspective on how judicial policies reflect and shape the broader political-legal landscape. The article concludes that SEMA No. 2 of 2023 is pivotal in balancing legal pluralism and social harmony and protecting religious and individual rights in Indonesia's dynamic legal system.